A common mutation in the 5,10-methylenetetrahydrofolate reductase gene affects genomic DNA methylation through an interaction with folate status - Friso, Simonetta; Choi, Sang-Woon; Girelli, Domenico; Mason, Joel B; Dolnikowski, Gregory G; Bagley, Pamela J; Olivieri, Oliviero; Jacques, Paul F; Rosenberg, Irwin H; Corrocher, Roberto; Selhub, Jacob (Proceedings of the National Academy of Sciences - PNAS, 2002)
DNA methylation, an essential epigenetic feature of DNA that modulates gene expression and genomic integrity, is catalyzed by methyltransferases that use the universal methyl donor S-adenosyl-l-methionine. Methylenetetrahydrofolate reductase (MTHFR) catalyzes the synthesis of 5-methyltetrahydrofolate (5-methylTHF), the methyl donor for synthesis of methionine from homocysteine and precursor of S-adenosyl-l-methionine. In the present study we sought to determine the effect of folate status on genomic DNA methylation with an emphasis on the interaction with the common C677T mutation in the MTHFR gene. A liquid chromatography/MS method for the analysis of nucleotide bases was used to assess genomic DNA methylation in peripheral blood mononuclear cell DNA from 105 subjects homozygous for this mutation (T/T) and 187 homozygous for the wild-type (C/C) MTHFR genotype. The results show that genomic DNA methylation directly correlates with folate status and inversely with plasma homocysteine (tHcy) levels (P < 0.01). T/T genotypes had a diminished level of DNA methylation compared with those with the C/C wild-type (32.23 vs.62.24 ng 5-methylcytosine/microg DNA, P < 0.0001). When analyzed according to folate status, however, only the T/T subjects with low levels of folate accounted for the diminished DNA methylation (P < 0.0001). Moreover, in T/T subjects DNA methylation status correlated with the methylated proportion of red blood cell folate and was inversely related to the formylated proportion of red blood cell folates (P < 0.03) that is known to be solely represented in those individuals. These results indicate that the MTHFR C677T polymorphism influences DNA methylation status through an interaction with folate status.